Pengaruh Perceived Risk dan Perceived Ease Of Use Terhadap Behavioral Intention Melalui Trust Sebagai Variabel Intervening (Pada Pengguna Shopeepay Generasi Milenial dan Z di Jakarta) - Azka Safira Eti Riyadi; Sudharto Prawata Hadi; Widayanto Widayanto (Universitas Diponegoro, 2024)
Abstract: Align with the advancement of digitalization in the financial system and payment methods in companies engaged in e-commerce, one of which is ShopeePay. However, based on survey data conducted by Populix in the